Adaptasi Masyarakat Siak Terhadap Perubahan Ekologinya - Yevita Nurti; M Rawa El Amdy El Amdy; Anto Ariyanto (Universitas Andalas, 2023)
This study described adaptation options in 4 villages in the Siak sub-district, Siak Sri Indrapura district, Riau province. Since the beginning of the reformation, Siak Sri Indrapura district was established which was expanded of Bengkalis district. Simultaneously also present there are plantation forest industries, oil palm plantations, immigration and urban development. This study is a qualitative study with a social history approach. The research was conducted from July 2022 to December 2020. Data was obtained through observation, in-depth interviews and FGDs at the village and Siak sub-district levels. Data were analyzed using a taxonomic analysis approach, the results of the analysis were written descriptively. The results of this study found that the presented of the Siak Sri Indrapura district, the plantation forest industry and the plantation industry as well as migrants caused the community to be uprooted from their agrarian economic culture. To be able to survive, the community carries out a long-term adaptation process through the transfer of sources of livelihood from agriculture to urban services and seizes the remnants of the urban economy and education. This study concludes that the pressure of ecological change forces people to adapt according to the resources they have. This study strengthens Bennett's adaptation theory that the adaptability of society does not exceed the resources they have.Key Word : Adaptation, Agriculture, Urban Services, Siak Community